Renewables, Preferential Trade Agreements and EU Energy Security - Rafael Leal-Arcas; Valentina Caruso; Raphaela Leupuscek (Laws, 2015)
A major aim of the international community is to decarbonize the economy. With renewables, international trade in energy is likely to increase. In turn, the international trading system can be a major vehicle towards moving away from fossil fuels to renewable energy. To this end, it can provide fair competition, economies of scale and knowledge transfer. This article analyzes the impact of European Union (EU) preferential trade agreements (PTAs) in addressing climate change mitigation and energy security by promoting renewables. Currently, there is a proliferation of PTAs; this trend seems irreversible and is likely to persist, given the current crisis in the multilateral trading system. We argue that the EU can, through its network of PTAs, move towards greater energy independence as renewable energy becomes increasingly economically viable. This article provides a thorough review of the renewable energy-related provisions in the EU’s current PTAs and recommends three tangible ways through which the EU could capitalize its vast network of PTAs to boost the renewable energy market.